Enhanced rational protein engineering to reduce viscosity in high-concentration IgG1 antibody solutions - Tyler J. Lefevre; Jenna G. Caldwell; Austin Gallegos; Qun Du; Erin Houston; Gilad Kaplan; Reza Esfandiary (mAbs)
Subcutaneous (SC) delivery of therapeutic antibodies can offer multiple benefits to patients and healthcare providers, including convenience, time savings, and cost reduction. To improve the SC injection experience, drug developers may seek a low injection volume (1–2 mL), which for some antibody drugs necessitates a high concentration solution (≥100 mg/mL) to meet dosage requirements. Several molecular-level challenges hinder the development of high concentration antibody drug products, including high viscosity caused by reversible self-association (RSA). Here, we take an enhanced rational design approach to reduce RSA via protein engineering. Using hydrogen-deuterium exchange mass spectrometry (HDX-MS), we identified potential self-interaction hotspots on the surface of an in-house IgG1 which has known viscosity issues at high concentration. Then, using in silico antibody modeling, we identified sites near the complementary-determining regions for targeting by rational mutagenesis, which included predicted patches of charge or hydrophobicity within or near peptides highlighted by HDX-MS. Screening of nearly 70 variants using dynamic light scattering (DLS) and affinity capture self-interaction nanospectroscopy (AC-SINS) at low concentration showed decreased self-interaction in many variants. Viscosity at 150 mg/mL was reduced by 70% for 13 variants, while two of these variants designed to reduce surface hydrophobicity were found to retain antigen binding compared to the parent antibody. DLS and AC-SINS measurements of self-association were found to correlate with viscosity at high concentration, reinforcing their utility as effective low-concentration screening tools for viscosity. This work demonstrates an enhanced rational mutagenesis strategy informed by the combination of HDX-MS for self-association and in silico predictions of surface properties. The resulting variants are a vast improvement on the parent antibody’s viscosity issues and offer insight into the mechanism of self-association.